Until We Have Faces: Memory, Self and Place in Education - Waldock, Michelle (Curtin University, 2019)
This thesis follows Hans-Georg Gadamer’s work leading the researcher into self-understanding, enriching her narratives of hermeneutical relationships in educational settings. Drawing upon Gadamer’s ideas of Dasein and “fusion of horizons” (2004, p.305) she weaves motes of memory in search of truths in her life. An islander traversing her island twice, in memory and in the present, she inhabits Gadamer’s “true locus” (p. 295), the intermediate position where interpretation dwells in its enfolding, unfolding potential.